PETA MEDNARODNA KONFERENCA CADAAD V BUDIMPEŠTI - Vičar, Branislava (Slavia Centralis, 2020)
The author reports on the course of the 5th International Conference CADAAD (Critical Approaches to Discourse Analysis across Disciplines), which took place at the Eötvös Loránd University (ELTE) in Budapest.